Analysis of the process of technology transfer in public research institutions: The Embrapa agrobiology case - Sheila Serafim da Silva; Paulo Roberto Feldmann; Renata Giovinazzo Spers; Martha Delphino Bambini (Innovation & Management Review, 2019)
Purpose - Empresa Brasileira de Pesquisa Agropecuária (Embrapa, the Brazilian Agricultural Research Corporation), owned by the Brazilian Government, is one of the most efficient agencies for promoting sustainable tropical agriculture in the world. However, although information is available, farmers do not always put the technologies and knowledge into practice. There is a large difference between the average productivity of farmers and crop or herd potential. Thus, this paper aims to describe and analyze the process of technology transfer of the Embrapa Agrobiology Unit. Design/methodology/approach The study reviewed the classical and diffusionist models of technology transfer (TT) in Brazilian agriculture and the role of the government in innovation. This was based on documentary research and structured interviews with four employees, supported by a structured roadmap composed of four categories for analysis: the role of TT; the organizational structure of the area; the TT strategies; and the ways of delivery, methods and tools of TT. By a qualitative approach, the results were treated through content analysis. Findings The results indicated that the area of TT at Embrapa went through a recent restructuring, which included the interchange and collective construction of knowledge (ICC) in its TT process, to turn entrepreneurship into reality. The company is dedicated to bringing knowledge to the most important people: farmers. This has been done through a participatory TT model, which has involved multiplier agents from the research stage to the transfer stage. Research limitations/implications Some limitations were found, among them, the fact that only internal members of Embrapa were interviewed, limiting the view of the TTICC staff and without knowing the multiplier agents' opinion and other actors involved in the process. In addition, it is a qualitative research that is subject to the interpretation of the researcher. Practical implications This study contributed to reflections about the TT process and how it can be used by different actors, along with the role of the State in innovation. Social implications In addition to contributing to the development of products, processes and technologies for the economic, social and environmental development of Brazil, Embrapa has been outstanding in generating knowledge for the advancement of science. Its results have had impacts not only nationally but also worldwide. Embrapa has played a key role in Brazilian agriculture as well as in livestock, mainly, in supporting governmental projects and in the implementation of public policies. Originality/value The aim of this study was achieved, as there was a possibility of describing and analyzing the technology transfer process at Embrapa Agrobiology Unit, located in the city of Seropédica, Rio de Janeiro. It is concluded that Embrapa has been committed to involving the farmer in the process of interchange, collective construction of knowledge and technology transfer. The farmer has become the focus of this process, reducing the development of "shelf" researches and increasing the participation of the farmer or of the multiplier agent. The importance of studying and knowing the process of technology and knowledge transfer to the public of interest should be highlighted, and especially the reasons why this technology or knowledge are often not adopted by the public. It was possible to identify that Embrapa has noticed the difficulties of farmers and realized that the best way the best way of transforming technological solutions and knowledge into innovation is by involving the farmer in the process of construction and of transfer. Thus, the farmer gives greater credibility to the technology or generated knowledge because this is something that he himself helped build. In the sphere of contemporary institutional knowledge management, Embrapa has had as its main point of departure the demand and the needs of society. For this, it has created means to ensure the participation of different actors because they signal the construction of technological solutions and of innovation and they are the ones who know the real situation. However, this is a recent progress within Embrapa that has evolved and generated results. Thus, research, science and technology institutions must go beyond technology transfer and must ensure the involvement, participation and interaction of the public of interest to promote significant change, social, economic and environmental development and transformation. Embrapa observed this from the referential framework that included technology transfer, interchange and the collective construction of knowledge.
Keywords: 650; Innovation; Technology transfer; Brazilian agriculture